65‐1: Invited Paper: Heavy‐Metal‐Free Electroluminescent Devices Based on Quantum Dots with Quasi‐Cubic Morphology. Issue 1 (28th June 2021) - Barrera, Diego; Ippen, Christian; Newmeyer, Ben; Kim, Daekyoung; DaRos, Jeffrey; Hotz, Charlie; Ma, Ruiqing
Abstract : Electroluminescent QD‐EL devices based on InP and ZnTeSe quantum dots are one of the most promising future display technologies. With improvement in synthesis, we have developed high quantum yield environmental‐friendly quantum dots and through device optimization we have achieved efficiencies of 21.0% and 13.5% for red and blue QD‐ELs, respectively. In this paper, we report on the impact of the quasi‐cubic morphology of quantum dots to device efficiency performance.